On adaptive estimation in partial linear models - Georgi Golubev; Wolfgang Härdle (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
The problem of estimation of the finite dimensional parameter in a partial linear model is considered. We derive upper and lower bounds for the second minimax order risk and show that the second order minimax estimator is a penalized maximum likelihood estimator. It is well known that the performance of the estimator is depending on the choice of a smoothing parameter. We propose a practically feasible adaptive procedure for the penalization choice.
urn:nbn:de:kobv:11-10064779
Keywords: 330; second order minimax risk; Adaptive estimation; penalized likelihood